2021
DOI: 10.3390/ijerph18042132
|View full text |Cite
|
Sign up to set email alerts
|

Housing and Community Environments vs. Independent Mobility: Roles in Promoting Children’s Independent Travel and Unsupervised Outdoor Play

Abstract: Children’s independent mobility (CIM) has declined dramatically in recent decades despite its benefits in facilitating childhood development, promoting physical activity, and combating the obesity epidemic. This US-based study examines the impacts of housing and neighborhood environments on two modes of CIM—home-based independent travel to non-school destinations and unsupervised outdoor play—while considering personal and social factors. A bilingual parent/guardian survey was distributed to public elementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The physical and social environment, where people live, work and play, are important social determinants of health [20,21]. Most studies show that a mixed-use neighborhood, public transportation, and complete streets that support walking and biking could encourage pedestrian travel and physical activity [22][23][24]. The social environment and recreation facilities also play an important role in increasing physical activity [7,12,24,25].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical and social environment, where people live, work and play, are important social determinants of health [20,21]. Most studies show that a mixed-use neighborhood, public transportation, and complete streets that support walking and biking could encourage pedestrian travel and physical activity [22][23][24]. The social environment and recreation facilities also play an important role in increasing physical activity [7,12,24,25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the policy level, urban planning literature identifies the role of zoning [32,37] and cross-agency collaboration [9,16,38,39] in promoting community health. At the community level, research shows that physical activity is related to community features, including mixed-use neighborhoods, transportation services, complete streets [22][23][24], recreation and social activity [7,12,24,25], perceptions of safety [27][28][29], and metro status [5,6,39]. We use demographic structure to capture the individual level, including income, race, age, and commuting time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thirtyone of the 47 papers base their findings on questionnaires, but few of these include children's perceptions of lighting or the lit environment, and if they do, the children are asked to answer a statement about how they perceive the lighting (e.g., positive or negative) or if lighting is present or not [e.g., Evenson et Another drawback in the papers is that the theoretical starting points are rarely explicitly stated, making it difficult to evaluate and interpret the findings. Recent systematic reviews on CIM have shown that it is associated with several attributes, such as socio-demographic, social and physical (134)(135)(136). It is therefore motivated to use theories that enable addressing the childenvironment relationship.…”
Section: Current Limitations In Understanding the Quality Of Outdoor ...mentioning
confidence: 99%
“…In addition, they conclude that for autonomous play, unsupervised by parents, parents' consent is important. To a large extent, this consent is based on the safety of the green area, as well as that of the route to that area, as perceived by parents (Qiu and Zhu, 2021;Visser and van Aalst, 2022). Furthermore, not only officially designated (green) playgrounds are likely to be relevant but also informal playgrounds (Visser and van Aalst, 2022), including undeveloped green areas, at least when trees are present (Janssen and Rosu, 2015).…”
Section: Number Of Childrenmentioning
confidence: 99%